Human tumor viruses: induction of three-dimensional alterations in the host genome structure - Minarovits, Janos (Frontiers in Microbiology, 2023)
Certain viruses called tumor viruses or oncoviruses are capable to change the gene expression pattern of distinct human or animal cell types in tissue culture, resulting in uncontrolled proliferation as well as a change in the social behavior of the infected cells: the oncovirus-transformed, immortalized cells are capable to form malignant neoplasms in suitable animal models. At present, seven human viruses are categorized as causative agents of distinct human malignancies. The genomes of human tumor viruses, typically encode viral oncoproteins and non– translated viral RNAs that affect the gene expression pattern of their target cells or induce genetic and epigenetic alterations contributing to oncogenesis. Recently, the application of chromatin conformation capture technologies and three-dimensional (3D) molecular imaging techniques revealed how the gene products or genomes of certain human tumor viruses interact with and induce alterations in the 3D host genome structure. This Mini Review aims to cover selected aspects of these developments. The papers, discussed briefly, describe how insertion of a novel viral binding site for the 3D genome organizer cellular protein CCCTC-binding factor (CTCF) into the DNA of T cells infected by human T-cell lymphotropic virus type 1 (HTLV-1) may contribute to lymphomagenesis, as well as how integration of high risk human papillomavirus genome into the host cell DNA may facilitate cervical carcinogenesis. Recent results regarding the interactions of cellular genomes with the episomal, chromatinized DNA genomes of oncogenic human herpesvirus, Epstein–Barr virus (EBV) will also be summarized, similarly to available data regarding contacts formed by episomal or integrated hepatitis B virus (HBV) DNA with host chromatin. Finally, a putative mechanism of hepatitis C virus (HCV) induced chromatin alterations will be presented, which may solve the riddle, how a cytoplasmic RNA virus without a viral oncogene could induce malingnant transfrormation of hepatocytes.